2022
DOI: 10.1080/1475939x.2022.2033307
|View full text |Cite
|
Sign up to set email alerts
|

Are we ready for virtual reality in K–12 classrooms?

Abstract: Virtual reality technology has existed since the late 1950s; however, its use in the educational sector has been limited because of the cost of the equipment, inaccessibility of the technology, issues of usability, and lack of appropriate educational content and educator training. New technological advances have resolved some of these limitations. Additionally, affordable virtual reality equipment that has been predominately used with adults shows compelling results, highlighting the potential of this technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 94 publications
1
18
1
Order By: Relevance
“…Finally, no statistically significant difference between non-immersive VR and immersive VR shares a critical insight into VR resource selection for teachers and school administrators. While immersive technology provides users with the most realistic experience, the costs associated with HMDs and possible health concerns can be barriers to integrating VR with children (Araiza-Alba, Keane, & Kaufman, 2022;Park et al, 2019). The study found not much difference in terms of knowledge development, classroom engagement, and historical empathy development between immersive VR and non-immersive VR.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, no statistically significant difference between non-immersive VR and immersive VR shares a critical insight into VR resource selection for teachers and school administrators. While immersive technology provides users with the most realistic experience, the costs associated with HMDs and possible health concerns can be barriers to integrating VR with children (Araiza-Alba, Keane, & Kaufman, 2022;Park et al, 2019). The study found not much difference in terms of knowledge development, classroom engagement, and historical empathy development between immersive VR and non-immersive VR.…”
Section: Discussionmentioning
confidence: 74%
“…The three-dimensional and immersive environments created by advanced VR technology can provide unique and engaging learning experiences that traditional learning resources (e.g., videos, books) cannot provide (Araiza-Alba et al, 2022). In particular, the use of VR in a social studies lesson has the possibility to create authentic learning environments where students interact with historical figures or explore historical events, potentially helping students better learn the historical concept of the time period that they are being studied (Kusuma, Adipranata, & Erandaru;2017;Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…VR in its simplest form can be defined as a computer-generated three-dimensional (3D) environment that allows the user to perceive content more realistically (Araiza-Alba et al, 2022). Furthermore, according to Carrozzino and Bergamasco (2010), VR is defined as three-dimensional practices where individuals can have real-life experiences in a virtual environment through interaction through a variety of tools, such as computers, mobile devices, databases and the internet.…”
Section: Vr Technology and 360° Video Vrmentioning
confidence: 99%
“…'Presence', on the other hand, is concerned with the experience of 'being there' and can be defined as a user response that depends on the individual and the context (Slater & Wilbur, 1997). VR environments can be divided into different computer-based system and Immersive Virtual Reality (IVR) groups according to the presence, feeling of immersion and interaction possibilities they provide (Araiza-Alba et al, 2022). Among these classifications, a sub-dimension of IVR: 360° video VR (or 360° video-based VR), has attracted attention, especially in recent educational literature, as a new technology that combines the strengths of 360° videos and VR (Mathende, 2021).…”
Section: Vr Technology and 360° Video Vrmentioning
confidence: 99%
“…Compared with immersive VR, the group collaboration, low costs, and convenience offered by IVR are more conducive to the mass adoption of this technology in education, such as in the case of units equipped with portable VR glasses (Vergara et al, 2017b). Moreover, evidence suggesting that IVR applications are beneficial for educational development is increasing (Mikropoulos and Natsis, 2011;Merchant et al, 2014;Araiza-Alba et al, 2022). Therefore, we have reason to believe that IVR experiential learning will become more common in educational settings.…”
Section: Introductionmentioning
confidence: 99%